Exploring the chemical composition, antioxidant, and antibacterial properties of milk thistle (Silybum marianum L.) - Iraqi, Oumayma; Aouji, Marouane; Oubihi, Asmaa; Imtara, Hamada; Noman, Omar M.; Mothana, Ramzi A.; Tarayrah, Mahmoud; Taboz, Youness; Habsaoui, Amar (Frontiers in Sustainable Food Systems, 2025)
IntroductionMilk thistle (Silybum marianum L.) is a wild plant commonly employed in traditional medicine, particularly for its recognized applications in treating liver diseases. However, there are limited data available on the phytochemical analysis and biological activity of the different parts of milk thistle cultivated in Morocco.Material and methodsThis study aims to examine and compare the phytochemical composition, the antioxidant activity and antibacterial activity of seeds, leaves and stems of milk thistle. The antioxidant activity has been carried out using 2,2-diphenyl-1- picrylhydrazyl (DPPH) and reducing power (RP) assays. The antibacterial activity was tested against seven bacteria, furthermore, we assessed the synergistic effects by evaluating the combination of these plant parts. High-Performance Liquid Chromatography with Ultraviolet Detection and Mass Spectrometry (HPLC-UV-MS) and Gas Chromatography–Mass Spectrometry (GC–MS) have been used to identify particular phytoconstituents in each component.Results and discussionSeeds and leaves showed comparable phenolic content However, leaves showed the highest flavonoid content with the highest antioxidant activity in both tests and no DPPH scavenging activity and reducing power activity detected in stems. Seeds showed the highest inhibition zone against S. aureus with an inhibition zone of 8 mm. The stems did not exhibit any inhibition zones against the tested bacteria except for K. pneumoniae where the inhibition zone was 6.60 mm. The combination of different parts did not show an increase in antibacterial activity. The extracts revealing a diverse array of bioactive compounds that enhance the antioxidant potential of milk thistle, emphasizing the distinct properties of each plant part. The closeness in phenolic content between seeds and leaves suggests that both parts could be valuable sources of antioxidants. However, despite the abundant phenolic content, the limited antibacterial activity indicates that the milk thistle’s extracts may be more pronounced in its antioxidant properties rather than its antibacterial effects.